Characterization and Construction of Linear Symplectic RK-Methods (Journal of Computational Mathematics, 1994)
A characterization of linear symplectic RK methods, which is based on the W-transformation of Hairer and Wanner, is presented. Using the characterization three classes of high order linear symplectic RK methods are constructed. They include and extend known classes of high order linear symplectic RK methods.